Effects of Moringa oleifera aqueous leaf extract in alloxan induced diabetic mice - Tuorkey, Muobarak J. (Interv Med Appl Sci, 2016)
OBJECTIVE: There is a lack of knowledge regarding the underlying mechanisms of the antidiabetic activity of Moringa oleifera. This study investigates the antidiabetic effect of M. oleifera and its impact on the immune tolerance. METHODS: Alloxan-induced diabetes model for mice was used. A dose of 100 mg/kg of Moringa extract was orally administered to diabetic treated mice. Glucose and insulin levels were evaluated to calculate insulin resistance. Total antioxidant capacity (TAC), creatinine, and blood urea nitrogen (BUN) levels were measured. The relative percentage of CD44, CD69, and IFN-γ was investigated by flow cytometry. RESULTS: In diabetic mice, insulin resistance by homeostasis model assessment of insulin resistance (HOMA-IR) was increased 4.5-fold than in the control group, and HOMA-IR was decreased 1.3-fold in the Moringa treatment group. The level of TAC was declined 1.94-fold in diabetic mice, and increased 1.67-fold in diabetic treated group. In diabetic mice, creatinine and BUN levels were significantly reduced 1.42- and 1.2-fold, respectively, in Moringa treatment mice. The relative percentage of CD44 was not changed in diabetic mice, but the relative percentage of CD69 was found to be increased. INF-γ was decreased 2.4-fold in diabetic mice and elevated in treated groups. CONCLUSION: Moringa may ameliorate insulin resistance, increase TAC, and improve immune tolerance.